ECMO in the Cardiac Catheterization Lab—Patient Selection Is Key - William Tracy; Brandon E. Ferrell; John P. Skendelas; Mayuko Uehara; Tadahisa Sugiura (Journal of Cardiovascular Development and Disease)
The use of extracorporeal membrane oxygenation (ECMO) has emerged as a rescue intervention for hemodynamically unstable patients and prophylactic intraprocedural hemodynamic support in the cardiac catheterization laboratory. The prompt initiation of ECMO provides immediate hemodynamic support and allows for the completion of bridging and/or life-saving interventions. However, there are no clinical practice guidelines for the use of extracorporeal support in this area. This review examines the role of patient selection and therapeutic intervention for extracorporeal support in the cardiac catheterization laboratory.